A Systematic Literature Review on Trends in the Use of Science Experiments in Online Learning Environments - Ubaidillah, Mujib; Marwoto, Putut; Subali, Bambang; Widiyatmoko, Arif; Cahyono, Adi Nur (International Review of Research in Open and Distributed Learning, 2025)
Experiments are considered to be essential components of science learning. This research aimed to investigate trends in the use of science experiments in online learning. A systematic literature review was carried out, with data sourced from the Scopus and Google Scholar databases. The reviewed documents were journal articles published between 2015 and 2022, with the keywords “science practicum,” “science experiments,” “distance learning,” “online learning,” and “hands-on science.” Using Harzing’s Publish or Perish software, 970 articles were found but only 32 were reviewed. The literature review followed a procedure adapted from the preferred reporting items for systematic reviews and meta-analyses (PRISMA), with articles reviewed based on predetermined criteria such as the year of publication, article source, practicum topics, research subjects, assessment methods, technology, and experiment design in online learning. In the results, various designs for online learning models, the technology used in science experiments, topics addressed, and appropriate assessment methods were identified. Trends included the extensive use of interactive simulation models in online science experiments, the use of virtual laboratories as a crucial technology, and the use of experiment reports to assess students. The analysis showed a sharp increase in the number of publications since the pandemic (2020) and that online science experiments might be carried out effectively by considering the characteristics of the material, matching the science curriculum, and using assessments that fulfill the objectives of science experiments.